Entrepreneurial education influence on the development of self-efficacy and entrepreneurial competences - Matos, Carolina Maria Furtado; Lizote, Suzete Antonieta; Teston, Sayonara de Fátima; Zawadzki, Patrick; Garra, Maria Cristina Almeida Gama (Revista de Administração da UFSM, 2020)
Purpose: This study aimed to evaluate entrepreneurship classes' influence on entrepreneurial self-efficacy and entrepreneurial competences in health academics. Design/methodology/approach: The model by De Noble, Jung, and Ehrlich (1999) was used to measure entrepreneurial self-efficacy and the model by Cooley (1990, 1991) to measure entrepreneurial competences. It is a quantitative, descriptive, and survey research. Two hundred sixty-seven undergraduate health students participated in the study. Statistical analysis used descriptive and correlational statistics with comparison tests. Findings: The results showed that the students who studied entrepreneurship presented higher self-efficacy and entrepreneurial competences, but there were no significant differences between those who studied and those who did not. Originality/value: This study presents the potential for promoting entrepreneurship in HEI for courses that are not directly associated with business management, especially health science courses. When analyzing the participants' behavioral characteristics, we seek to deepen the discussion on the central themes of the study and promote reflections on the importance of entrepreneurial education for the development of future health professionals.